Association and interactions between mixed exposure to trace elements and the prevalence of kidney stones: a study of NHANES 2017–2018 - Xiao Wang; Jia Zhang; Zhibin Ma; Yaya Yang; Ying Dang; Shuting Cao; Xiaoru Shi; Changping Ouyang; Jinhua Pan; Xiaobin Hu (Frontiers in Public Health, 2023)
BackgroundThe association between exposure to trace elements mixture and the prevalence of kidney stones and the interactions between elements are unclear. The aim of this study was to explore the association between exposure to trace elements mixture and the prevalence of kidney stones and the interactions between the elements.MethodsA total of 1,244 participants (139 kidney stone formers and 1,105 non-stone former participants) in NHANES 2017–2018 were included. The exposure to trace elements was evaluated by measuring their concentration in urine samples. Three methods, Logistic regression, quantile-based g computation (qgcomp), and Bayesian kernel machine regression (BKMR), were used for analysis.ResultsAccording to the results from qgcomp and BKMR, a negative association was found between exposure to the 13 trace elements and the prevalence of kidney stones [OR = 0.50 (0.32, 0.78)]. Subgroup analysis revealed that Co, As, and iodine in the whole population, Co, As, and Ni in males, and Cs, iodine, and Sb in females, were most strongly associated with kidney stones. Kidney stone was found to be positively correlated with Co and negatively correlated with the other elements. Besides, there were significant interactions between Ni and Pb in the whole population, Co and iodine in males, and Pb and iodine in females.ConclusionThere was a negative association between exposure to the mixture of 13 trace elements and the prevalence of kidney stones.